Choriocarcinoma Syndrome as an Initial Presentation of Testicular Cancer - Carlos Eduardo Salazar-Mejía; María Elena García-Gutiérrez; María Inés Contreras-Salcido; Carlos Javier Rodríguez-Álvarez; Blanca Otilia Wimer-Castillo; Jackeline Grace Lara-Campos; Edio Llerena-Hernández; José Luis González-Vela; David Hernández-Barajas (Case Reports in Oncological Medicine)
Choriocarcinoma syndrome (CS) is a rare clinical entity within the spectrum of nonseminomatous germ-cell tumors (NSGCT). It is characterized by the abrupt establishment of rapidly progressive and hemorrhagic tumors associated with very high levels of the beta fraction of human chorionic gonadotropin (β-hCG) and with a very poor prognosis, particularly in patients with β-hCG values above 50,000 IU/L. We present the case of a 17-year-old man with a sudden onset nonmassive hemoptysis. Physical examination revealed a right testicular mass. Imaging studies showed metastatic lung, bone, and retroperitoneal disease. β-hCG serum levels were 222,493.21 IU/L, AFP 1.56 ng/mL, and DHL 457 IU/L. Histopathological study after right radical orchiectomy showed a mixed germ-cell tumor. Based on poor-risk characteristics, chemotherapy was started with an adequate clinical response. Physicians should be aware of the potential complications of CS in the treatment of testicular cancer with high β-hCG levels since they could be associated with a rapidly progressive and high-volume disease. Patients in this category should be referred to the centers experienced in the treatment of advanced germ-cell tumors. Due to the severity of the presentation, hemodynamic monitoring, ideally in an intensive care unit, is essential as well as timely administration of cytotoxic treatment.